Legal foundations of the organization and activities of the Ukrainian SSR police in 1949–1950s - О. V. Brusakova; V. A. Hrechenko (Law and Safety)
The main aspects of the structure of the police in 1949–1950 and the main directions of its activity have been studied. The changes in the Criminal Procedure Code of the Ukrainian SSR guided by the police in the performance of their law enforcement functions have been highlighted. It has been noted that the structure of local police bodies in the regions of Ukraine in the post-war period was of the same type, but could differ depending on operational conditions in the number of regular units. The most important change in the structure of the Ministry of Internal Affairs during this period was the transfer of the police to the Ministry of State Security in October 1949. The activities of the police were controlled and regulated by decisions and resolutions of the Communist Party of Ukraine. First of all, it concerned the selection of personnel and education of police personnel. The central governing body of the police was the Main Directorate of the Police. The police departments of the Union republics, regions, large cities, district departments and branches, military units of the police were subordinate to it. At the same time, the heads of these police bodies held the positions of deputy people’s commissars of internal affairs of the republics, heads of regional NKVD (People’s Commissary of Internal Affairs) departments, heads of departments and NKVD departments of cities and districts.